Phonetic evaluation of the edentulous patient correlated with the various settings of the artificial teeth - Bortun Cristina; Leretter Marius; Sandu Liliana; Dodenciu Dorin; Draganescu Gheorghe; Samoila Christian (Serbian Medical Society - Dental Section, Belgrade, 2004)
The dentist's preoccupation concerning the phonetic rehabilitation of the edentulous patient emanates from the practical findings about the consonant alteration during the speech process. The aim of this study was to assess the phonetic alterations in complete denture wearers caused by position, size and material (resin or ceramics) of the frontal artificial teeth. This was performed using the static palatographies and spectrograms, which evaluated the most important spaces for the phonetic modulation, in relation to various settings of the artificial teeth.